Water savings in irrigated agriculture - a framework for assessing technology and management options to reduce water losses - Hess, Tim M.; Knox, Jerry W. (IP Publishing, 2013)
Water savings in agriculture often refer to reducing the amount of water abstracted or diverted and used for different purposes. However, this is not the only option as reductions in water use can also be achieved by using appropriate techniques for irrigation, applying relevant management practices, using water from alternative sources or influencing behaviour, for example via awareness-raising, dissemination of best practices, regulation, water pricing and/or using financial incentives. Whilst these options or responses will help reduce pressure on water resources, if implemented in isolation they limit the extent to which water is actually ‘saved'. More often they need to be considered as part of a broader integrated approach to water management. This paper presents a framework for identifying areas where scope for achieving water savings exist, and then briefly reviews the possible means of action and constraints to implementation. The framework is intended to inform polices aimed at improving the sustainability and allocation of water to irrigated agriculture.
Keywords: abstraction; consumptive use; efficiency; soil; water resources